2020
DOI: 10.1002/cncy.22249
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of brush biopsy–based cytology for the early detection of oral cancer and precursors in Fanconi anemia

Abstract: BACKGROUND: Individuals with Fanconi anemia (FA) have a 500-fold to 700-fold elevated risk, much earlier onset, and limited therapeutic options for oral squamous cell carcinoma (SCC) compared with the general population. The early detection of SCC, or preferably its precursors, is mandatory to retain curative therapeutic options. Due to frequent synchronic and metachronic oral lesions, tissue biopsies, as usually recommended by guidelines, often are not feasible. In the current study, an alternative strategy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 38 publications
1
63
0
1
Order By: Relevance
“…This landmark study included 1233 brush biopsies from an unprecedentedly large cohort of 713 FA patients. They concluded that careful inspection of the oral cavity followed by brush biopsy of suspected lesions detects 63% of SCCs and its precursors at an early stage and negative cytology, especially when combined with DNA ploidy analysis, resulted in a benign course with a high specificity [ 14 ]. The benefits of brush biopsies in FA include low cost and minimal invasiveness in addition to potentially excellent sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…This landmark study included 1233 brush biopsies from an unprecedentedly large cohort of 713 FA patients. They concluded that careful inspection of the oral cavity followed by brush biopsy of suspected lesions detects 63% of SCCs and its precursors at an early stage and negative cytology, especially when combined with DNA ploidy analysis, resulted in a benign course with a high specificity [ 14 ]. The benefits of brush biopsies in FA include low cost and minimal invasiveness in addition to potentially excellent sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with FA have increased predisposition to squamous cell carcinoma of the anogenital tract and head and neck region [11]. In addition, many studies have linked FA to oral cancer [7,12,13] and some have assessed the risk of developing oral cancer [14,15].…”
Section: Oral Manifestations Of Famentioning
confidence: 99%
“…The MN frequency was found to be such a good biomarker of chromosomal fragility in epithelial cells that it is already being studied as an endpoint in clinical trials for chemoprevention interventions [120]. The second one studied brush biopsy specimens from oral lesions of patients with FA and showed that DNA aneuploidy is a good biomarker for oral epithelial dysplasia or SCC [121].…”
Section: Bone Marrow Abnormalitiesmentioning
confidence: 99%